THE RELATIONSHIP BETWEEN AGE, PARITY, AND PREGNANCY INTERVAL WITH HEMOGLOBIN LEVELS IN THIRD TRIMESTER PREGNANT WOMEN AT PRAKTIK MANDIRI BIDAN OF FAUZIAH HATTA - Mardia Sari, Era; Indah Syafriani, Elvina; Hariani, Desi (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Hemoglobin levels are one of the hematological parameters that undergo changes during pregnancy. During pregnancy, plasma volume increases by approximately 40-45%, starting progressively in weeks 6-8 of gestation and reaching its peak at weeks 32-34. Concurrently, renal erythropoietin stimulates the increase in red blood cell count by 20-30%. However, the increase in red blood cells is not proportional to the increase in plasma volume, leading to hemodilution and a decrease in hemoglobin levels. This study aims to determine the relationship between age, parity, and pregnancy interval with hemoglobin levels in third-trimester pregnant women. The sample in this study consisted of 40 respondents, all third-trimester pregnant women who attended prenatal visits between September and November 2023. The analysis method used in this study was Pearson correlation. There are three analyses in this study: first, the analysis of the relationship between age and hemoglobin levels showed a p-value of 0.026, which is less than α (0.05), indicating a significant relationship between age and hemoglobin levels in pregnant women. Second, the analysis of the relationship between parity and hemoglobin levels showed a p-value of 0.736, which is greater than α (0.05), meaning there is no relationship between parity and hemoglobin levels in pregnant women. Third, the analysis of the relationship between pregnancy interval and hemoglobin levels showed a p-value of 0.012, which is less than α (0.05), indicating a significant relationship between pregnancy interval and hemoglobin levels in pregnant women.